The Anthropocene as a Regime of Historicity: Ontological and Epistemological Challenges for Historiography - Vera Castañeda, Julio Ricardo (Revista de Historia Social y de las Mentalidades, 2024)
This paper analyzes the Anthropocene as a new regime of historicity, as recently suggested by François Hartog. It evaluates the contributions and limitations of this interpretative framework for historical time, its connection to conceptual history, and the intellectual influences Hartog draws upon. The paper proposes that the material experience of the breakdown of time and space challenges understanding the Anthropocene as purely anthropocentric. Thus, the temporality of the Anthropocene presents ontological and epistemological challenges relevant to historiography, particularly in the reconceptualization of categories such as "world" and "nature."